ANALYSIS OF INCOME ON THE CANDLENUT FARMING IN RAIMANUS VILLAGE, RAIMANUK DISTRICT, BELU REGENCY - Maria H. Ikun Moruk; Werenfridus Taena; Umbu Joka (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
This study aims to determine (1). general description of candlenut farming in Raimanus Village, Raimanuk District, Belu Regency, (2). To find out the analysis of candlenut farming income in Raimanus Village, Raimanuk District, Belu Regency (3). To find out the relative advantages of candlenut farming in Raimanus Village, Raimanuk District, Belu Regency. The research was conducted in November - December 2019. The data collection technique used a survey method with primary data and secondary data. The sample used in the study was 30 respondents. The data analysis method in the study is in the form of a descriptive model, income analysis, and benefit cost ratio (BCR), the net result in 2018 is Rp. 116,221,453, relative profit = 2.42 so that candlenut farming in Raimanus Village, Raimanuk District, Belu Regency is profitable/provides benefits to farmers in Raimanus Village.